Multifunctional Ultra‐Bright Plasmonic Gold@Fluorescence Nanoprobe for Biomedical Applications - Caiping Ding; Wenjing Li; Xiaolin Huang; Ben Zhong Tang; Youju Huang (Aggregate)
ABSTRACT Metal‐enhanced fluorescence (MEF) represents a captivating phenomenon that transpires when fluorophores are situated in close vicinity to the surface of metallic nanostructures, leading to a nuanced augmentation of their fluorescent characteristics. Given its efficacy in enhancing excitation rates, quantum yield, and photostability, MEF has firmly established itself as a highly valuable tool for augmenting biosensor sensitivity, bioimaging clarity, and intensifying therapeutic responses. Notably, plasmonic gold nanostructures, inherently advantageous for MEF, have been widely utilized in signal amplification, fluorescent labeling, and theranostics. In this endeavor, we undertake a comprehensive examination of MEF‐enabled gold nanostructures, meticulously analyzing their fundamental enhancement mechanisms, crucial influencing factors, and diverse modes of enhancement. Furthermore, we spotlight the exemplary applications of these nanostructures in biosensing, bioimaging, and theranostics, underscoring their revolutionary potential. Ultimately, we offer a glimpse into the future prospects for improvement and the challenges that beset gold‐based MEF. Our attention is steadfastly directed toward the essential scientific questions and technical hurdles that remain to be surmounted, inviting readers to partake in an exciting exploration of this dynamic and promising field.